2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31234
|View full text |Cite
|
Sign up to set email alerts
|

What Does Hidden Curriculum in Engineering Look Like and How Can It Be Explored?

Abstract: Her multiple roles as an engineer, engineering educator, engineering educational researcher, and professional development mentor for underrepresented populations has aided her in the design and integration of educational and physiological technologies to research 'best practices' for student professional development and training. In addition, she is developing methodologies around hidden curriculum, academic emotions and physiology, and engineering makerspaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Second, our data only enables us to draw conclusions about students' espoused beliefs, which may or may not align with their more deeply-held or implicit beliefs. This is a limitation because we know that people are often unaware of their implicit beliefs, even though they inform our conduct in real-world settings (Connors and Halligan 2015;Smith 2016), and these more deeply-held beliefs can be transmitted through the hidden curriculum (Bejerano and Bartosh 2015;Polmear et al 2019;Villanueva et al 2018). Third, we also acknowledge that courses such as capstone design provide students with limited time to work on their projects and, therefore, might affect the decisions students make when working on their design projects.…”
Section: Limitationsmentioning
confidence: 98%
“…Second, our data only enables us to draw conclusions about students' espoused beliefs, which may or may not align with their more deeply-held or implicit beliefs. This is a limitation because we know that people are often unaware of their implicit beliefs, even though they inform our conduct in real-world settings (Connors and Halligan 2015;Smith 2016), and these more deeply-held beliefs can be transmitted through the hidden curriculum (Bejerano and Bartosh 2015;Polmear et al 2019;Villanueva et al 2018). Third, we also acknowledge that courses such as capstone design provide students with limited time to work on their projects and, therefore, might affect the decisions students make when working on their design projects.…”
Section: Limitationsmentioning
confidence: 98%
“…A series of emerging studies have revealed similar findings (e.g. Bakht 2018;Kovalchuk et al 2017;Lutz 2017;Paretti et al 2017;Villanueva et al 2018).…”
Section: Research On Engineering Workplace Transitionsmentioning
confidence: 68%
“…Future studies may also triangulate viewpoints of experienced instructors with that of senior management, novice teachers, instructional designers, and students to establish a more comprehensive understanding of the issues discussed. Work to explore the invisible curriculum, such as in the work of Villanueva et al (2018), can also be undertaken to uncover and establish the competencies within it and, in turn, help pave the way to bringing them into the forefront of engineering education.…”
Section: Discussionmentioning
confidence: 99%